A taste for death [videorecording (DVD)] - James, P. D.; Marsden, Roy, 1941-; Hiller, Wendy, 1912-2003; Ward, Simon, 1941-2012; Davies, John Howard, 1939-2011; James, P. D. (P.D. James the essential collection, 2008)
"Dark secrets lurk behind the respectable facade of a government minister's household in a complex case of multiple murder"--Koch Entertainment booklet.